The art and science of consultations in bovine medicine: use of modified Calgary – Cambridge guides, Part 2 - Amanda Nicole Carr; Roy Neville Kirkwood; Kiro R. Petrovski (Macedonian Veterinary Review, 2023)
This article, part 2 of a 2-part series, describes the next two steps in the application of the Modified Calgary-Cambridge Guides (MCCG) to consultations in bovine medicine, ‘explanation and planning’, and ‘closing the consultation’, and introduces concepts that are associated with all the components of the guide, ‘building the relationship with the client’ and ‘providing structure to the consultation’. Part 1 introduced the aim and framework of the MCCG which enables the practitioner to gain an insight into the client’s understanding of the problem, including understanding aetiology, epidemiology and pathophysiology. Part 2 introduces the framework that provides the opportunity to understand the client’s expectations regarding the outcome, their motivation and willingness to adhere to recommendations. It also describes how to engage and acknowledge the client as an important part of the decision-making process, how to establish responsibilities of both the client and practitioner, and how to reach out to the client at the conclusion of the consultation to make certain that the client’s expectations were met.